Food Waste to Energy through Innovative Coupling of CHP and Heat Pump - Jan Drofenik; Danijela Urbancl; Darko Goričanec; Zdravko Kravanja; Zorka Novak Pintarič (Energies, 2023)
This paper presents the conceptual design of a technological solution for the efficient conversion of food waste into heat and power. The distribution and composition of food loss and waste at different stages of the food supply chain in Slovenia and their potential for biogas production were determined. It was found that more than 50% of food waste comes from households. Therefore, a small plant was designed to convert food waste into biogas, which was innovatively coupled with a combined heat and power (CHP) unit and a heat pump. This doubles the amount of heat generated compared to conventional cogeneration. Based on the capacity of a micro commercial CHP unit, 3330 households (about 8000 residents) would supply food waste. The heat generated could replace 5% of the natural gas used for domestic water heating. The payback period would be 7.2 years at a heat price of about 80 EUR/MWh, however, for municipalities with more than 40,000 inhabitants the payback period would be reduced to less than 3 years. The cost price of the heat generated by this system would be about 25 EUR/MWh, taking into account the government subsidy for the operation of the CHP unit.